2018
DOI: 10.1016/j.cub.2018.08.065
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Oscillatory Phase for Pattern Reactivation during Memory Retrieval

Abstract: Highlights d We show evidence for theta phase encoding-retrieval models in human EEG data d Neural indices of memory reactivation from pattern classifiers fluctuate at 7 or 8 Hz d Times of maximal memory reactivation are preceded by a consistent theta phase d Optimal phase for encoding and retrieval is shifted by approximately 180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
119
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 70 publications
(107 reference statements)
13
119
0
1
Order By: Relevance
“…For example, Clouter, Shapiro, and Hanslmayr () demonstrated that two stimuli presented at the same phase of theta are more likely to be successfully encoded than two stimuli that are presented at opposing phases, indicating that associative memory formation varies as a function of theta phase. Moreover, Kerrén, Linde‐Domingo, Hanslmayr, and Wimber () demonstrated that neural evidence for retrieved stimuli fluctuate at approximately 7 Hz, suggesting that episodic memory retrieval is also dependent on theta phase.…”
Section: A Role For Neural Oscillationsmentioning
confidence: 99%
“…For example, Clouter, Shapiro, and Hanslmayr () demonstrated that two stimuli presented at the same phase of theta are more likely to be successfully encoded than two stimuli that are presented at opposing phases, indicating that associative memory formation varies as a function of theta phase. Moreover, Kerrén, Linde‐Domingo, Hanslmayr, and Wimber () demonstrated that neural evidence for retrieved stimuli fluctuate at approximately 7 Hz, suggesting that episodic memory retrieval is also dependent on theta phase.…”
Section: A Role For Neural Oscillationsmentioning
confidence: 99%
“…Recent scalp (Kerrén et al, 2018; Michelmann et al, 2016) and intracranial EEG studies (Staresina et al, 2016; Zhang et al, 2015) further demonstrated the particular potential of frequency-transformed activity patterns in identifying memory-relevant reactivation of item-specific signatures. For example, Michelmann et al (2018) showed that desynchronized low-frequency brain oscillations carried stimulus-specific temporal activity patterns during an associative memory task.…”
Section: Introductionmentioning
confidence: 99%
“…The distance to the hyperplane indicates the amount of classifier evidence present in the data. Distance measures have previously been used as a measure of model activation (23,32) and have been linked to reaction time measurements (33). For each perception model and for each imagery trial, we identified the time of the absolute peak distance (23).…”
Section: Resultsmentioning
confidence: 99%